Exchange Rate Regimes in Central, Eastern and Southeastern Europe : A Euro Bloc and a Dollar Bloc? - Slavov, Slavi (IMF Working Papers; Working Paper ;, 2017)
There are 13 countries in Central, Eastern and Southeastern Europe (CESEE) with floating exchange rate regimes, de jure. This paper uses the framework pioneered by Frankel and Wei (1994) and extended in Frankel and Wei (2008) to show that most of them have been tracking either the euro or the US dollar in recent years. Eight countries, all of them current or aspiring EU members, track the euro. Of the five countries keying on the US dollar in various degrees, all but one belong to the Commonwealth of Independent States. The paper shows that the extent to which each country's currency tracks the euro (or the dollar) is correlated with the structure of its external trade and finance. However, some countries appear to track the EUR or USD to an extent which appears inconsistent with inflation targeting, trade or financial integration, or the extent of business cycle synchronization. The phenomenon is particularly pronounced among the countries in the CESEE euro bloc, which may be deliberately gravitating around the euro in anticipation of eventually joining the Euro Area.